Clinical effectiveness and long-term retention of abatacept in elderly rheumatoid arthritis patients: Results from a multicenter registry system. Issue 6 (2nd November 2019) - Takahashi, Nobunori; Kojima, Toshihisa; Kida, Daihei; Kaneko, Atsushi; Hirano, Yuji; Fujibayashi, Takayoshi; Yabe, Yuichiro; Takagi, Hideki; Oguchi, Takeshi; Hanabayashi, Masahiro; Kato, Takefumi; Funahashi, Koji; et al.
Abstract: Objective: To study the clinical effectiveness and long-term retention rate of abatacept (ABA) in elderly rheumatoid arthritis (RA) patients in daily clinical practice. Methods: A retrospective cohort study was performed using data from a multicenter registry. Our study population comprised 500 consecutive RA patients treated with ABA. We compared clinical effectiveness and ABA retention rates between the Young (≤62 years), Middle (62 to 72 years), and Elderly (≥72 years) groups. We also performed separate examinations to identify predictive factors for ABA discontinuation in those with versus those without concomitant methotrexate (MTX) treatment. Results: Mean age was 52.7 years in the Young group, 67.7 years in the Middle group, and 78.1 years in the Elderly group. No significant group-dependent differences were found in mean DAS28 score, categorical distribution of DAS28, and EULAR response rate across the 52 weeks. The ABA retention rates at three years as determined by the Kaplan–Meier method were similar in all three groups. Patient age was not a significant predictor of ABA discontinuation due to adverse events in patients with concomitant MTX; however, it was found to be a significant predictor for those who did not use MTX (Cox hazard model). Conclusion: ABA would be a reasonable treatment option for elderly RA patients from the viewpoints of both clinical effectiveness and long-term retention. However, physicians should watch carefully for any serious adverse reactions in elderly RA patients with intolerance to MTX.